Evaluación de la extracción de Genipina para la producción de colorante azul a partir del fruto de la Genipa Americana L. (2021)
The present work has as its purpose the elaboration of a blue dye taking advantage of the jagua destined for the food industry as an alternative to artificial colorants that, today, present safety problems. In the development of this project, a sensory, physicochemical and proximal of the fruit of the Genipa Americana L. tree, the latter will be studied to be used in a solid-liquid extraction by means of a conventional technique Soxhlet, handling high purity ethanol for different amounts of raw material. In relation to the above, some physicochemical characteristics were determined in the extracts obtained by establishing the most favorable conditions in order to concentrate and identify a secondary metabolite known as genipin. In reference to the pre-purification of the analyte, two different methods were carried out with the purpose of Evaluate extraction performance for aglycone concentration.